Pendampingan Kegiatan English Club Mahasantri Pondok Pesantren di Kota Metro Melalui Program Peningkatan Kemampuan English Proficiency (Toefl) - Nurul Puspita; Umar A. Hasyim (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
TOEFL is known to have a very high level of difficulty. Grammar and vocabulary become a heavy burden for students. Weak understanding in these two skills will hinder their understanding to answer the Listening, Structure, Written Expression, and Reading sections. Facing this problem, the Ma'arif NU Metro Lampung Institute of Islamic Religion organizes an English Language training program assistance (TOEFL) for Islamic boarding school students in the city of Metro, especially those who are studying at IAIMNU Metro. This Mentoring Program is expected to be able to help students to improve their communication skills both orally and in writing in English in the scope of academic understanding through the TOEFL. In this mentoring activity, it is hoped that they will be motivated and equipped with learning and strategies to analyze and answer questions in the TOEFL system.